Tinea Corporis Et Cruris - M. Mimbar Topik; Sofwatul Marfiyah (Detector: Jurnal Inovasi Riset Ilmu Kesehatan, 2023)
MS, a 15-year-old boy, ethnic Acehnese, address Paya Bakong with number RM 024395, was taken by his parents to the skin and genital polyclinic at Cut Meutia Hospital on Monday, 10 October 2022. Autoanamnesis was carried out with the elderly, the patient found that the main complaint was reddish spots, scaly, well defined with active lesion edges and central healing, accompanied by itching in the abdominal area, since 2 months ago. A reddish spot appears with white scales the size of a coin on the stomach, the spot gradually grows wider and grows to the size of a palm. Then the spots also appeared on the hands, left leg and left groin. The red spots feel very itchy, especially when sweating and hot air and get better after bathing. According to the patient, itching is not affected by the food consumed every day. The patient only noticed a reddish spot 2 months ago, which prompted him to see a doctor. The patient lives in a dormitory because he attends a boarding school. History of bathing and changing clothes 2 times a day, towels are used alone and the clothes that the patient often uses are shirts and frequent outdoor activities. The patient said that he often sweats profusely, but does not immediately change his clothes. Dermatological status in the lateral abdominal region dextra et sinistra et manus sinistra et inferior extremitas sinistra et cruris sinistra shows hyperpigmented erythematous macule-patches, firm boundaries, multiple, irregular with active edges and central healing, nummular-plaque size, partly covered with medium scale with a white layer. Based on history, physical examination, dermatology, the working diagnosis in this patient is tinea corporis et cruris. Treatment was given oral drug itraconazole 2x100 mg and miconazole cream 15gr 2x1 applied in a thin layer. As well as being given an explanation of the disease, its causes, treatment options, prevention and education for body hygiene, not using clothes towels with other family members.